Haydn: the early years 1732-1765 - Landon, H. C. Robbins 1926-2009 (London Thames and hudson, 1980)
This volume, the first of five, covers the period of Joseph Haydn's childhood and early creative years; it sets the scene - both historical and musical - in Europe (and especially Austria), and provides a detailed account of Haydn's family background and the circumstances in which he grew up. In addition to the chronicle of events and separate discussion of his works - a basic formula adopted for all five volumes of this biography - a vital ingredient of this first volume is a consideration of the principal musical influences in Haydn's youth, with examples taken from works (by composers now largely forgotten) which he would certainly have known.